Occurrence of hot days in north-western Poland in the years 1986–2015 - Więcław, Mirosław (Journal of Education, Health and Sport, 2017)
The article discusses annual, multi-seasonal and spatial variability of the occurrence of hot days (tmax³30oC) in north-western Poland. The study used meteorological data gathered at ten gauging stations in the years 1986–2015. Calculations were conducted regarding the number of hot days in individual years, which allowed for determining trends of changes. Annual distribution of hot days is presented against months divided into decades. Furthermore, the analysis accounts for the intensity of temperatures at individual stations, as well as length of undisrupted sequences of hot days. The author also took upon himself to indicate air masses that contribute to the occurrence of such days.